LIM and SH3 protein 1 (LASP‐1): A novel link between the slit membrane and actin cytoskeleton dynamics in podocytes. Issue 4 (21st February 2020) - Lepa, Carolin; Möller‐Kerutt, Annika; Stölting, Miriam; Picciotto, Cara; Eddy, Mee‐Ling; Butt, Elke; Kerjaschki, Dontscho; Korb‐Pap, Adelheid; Vollenbröker, Beate; Weide, Thomas; George, Britta; Kremerskothen, Joachim; et al.
Abstract: The foot processes of podocytes exhibit a dynamic actin cytoskeleton, which maintains their complex cell structure and antagonizes the elastic forces of the glomerular capillary. Interdigitating secondary foot processes form a highly selective filter for proteins in the kidney, the slit membrane. Knockdown of slit membrane components such as Nephrin or Neph1 and cytoskeletal adaptor proteins such as CD2AP in mice leads to breakdown of the filtration barrier with foot process effacement, proteinuria, and early death of the mice. Less is known about the crosstalk between the slit membrane‐associated proteins and cytoskeletal components inside the podocyte foot processes. Our study shows that LASP‐1, an actin‐binding protein, is highly expressed in podocytes. Electron microscopy studies demonstrate that LASP‐1 is found at the slit membrane suggesting a role in anchoring slit membrane components to the actin cytoskeleton. Live cell imaging experiments with transfected podocytes reveal that LASP‐1 is either part of a highly dynamic granular complex or a static, actin cytoskeleton‐bound protein. We identify CD2AP as a novel LASP‐1 binding partner that regulates its association with the actin cytoskeleton. Activation of the renin‐angiotensin‐aldosterone system, which is crucial for podocyte function, leads to phosphorylation and altered localization of LASP‐1. In vivo studies using the Drosophila nephrocyte model indicate that Lasp is necessary for the slit membrane integrity and functional filtration.